EKSPRESI KREATIF SISWA SMA SANTO YOSEP SURAKARTA DALAM PELATIHAN TARI - Hartanto Hartanto (Institut Seni Indonesia Surakarta, 2016)
This article talks about creative expression of students in SMA (Senior High School) Santo Yosep Surakarta in dance training. To gain the studentsâ€™ creative expressions, the writer executes the following stages: dance appreciation, dance training, and implementation of their creative expressions into dance works. The creativity development is formed by gaining the studentâ€™s creative ability through the direct guiding. The students are given a freedom and discretion in body processing and express it in a performing art. This is supposed to give an understanding of creativity basic foundation, to form a creative media, to perform the creative works, and to document audio visual in order to beÂ used as a reference in dance studying in Senior High School. Key words : creative expression, dance, student of Senior High School, and training.